“Estimulación temprana y su influencia en el desarrollo de la motricidad fina y gruesa de los niños del centro de cuidado infantil los inquietos, del barrio los altares de la ciudad de riobamba, provincia de chimborazo en el periodo de enero a julio del 2010”. - Cuenca Cuji, Mayra Jimena (2010)
Early stimulation is all stimuli that give the child the experience you need to develop their skills according to age from birth to 6 years of age. Children attending child care centers are most vulnerable to risk getting their development are in the cognitive, motor, languagandsociemotional due to inadequate implementation of early stimulation by the caring mothers. Therefore this research has been conducted in order to determine the incidence of children with delays and risks in their development. In this research work was carried out an observation guide to children and mothers carers’ survey, whose results allow identifying the number of children who showed abnormal development and mothers the level of knowledge about early stimulation and their implementation. As an additional contribution is made and a training guide early stimulation directed to mothers of child care to prevent complications of restless development and growth in children.